1974
DOI: 10.1063/1.1655364
|View full text |Cite
|
Sign up to set email alerts
|

Transparent heat-mirror films of TiO2/Ag/TiO2 for solar energy collection and radiation insulation

Abstract: Transparent heat-mirror films of TiO2/Ag/TiO2 on glass with a visible transmission of 84% (at 0.5 μm) and an infrared reflectivity of 98–99% (at 10 μm) have been fabricated by rf sputtering. Initial tests indicate that the films are thermally stable in air at 200°C and inert to water attack. Because of their excellent optical properties and apparent stability, these transparent heat-mirror films offer great promise for use in solar-thermal power conversion and as transparent thermal insulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(75 citation statements)
references
References 6 publications
1
73
0
1
Order By: Relevance
“…The glass globe must be thin and have high transmissivity for light in the visible wave lengths; it should be internally coated to maximize reflection of radiation from the receptor surface (7). As in a light bulb, the glass enclosure will get hot and must be insulated at the base.…”
Section: Fig 4 Collector Efficiency and Thermodynamic Cycle Efficiencymentioning
confidence: 99%
“…The glass globe must be thin and have high transmissivity for light in the visible wave lengths; it should be internally coated to maximize reflection of radiation from the receptor surface (7). As in a light bulb, the glass enclosure will get hot and must be insulated at the base.…”
Section: Fig 4 Collector Efficiency and Thermodynamic Cycle Efficiencymentioning
confidence: 99%
“…Another alternative to ITO as transparent conductors is the use of dielectric/metal/dielectric (D/M/D) multilayers, which suppress the reflection of the metal layer and achieve selective high transparent effect [14]. In 1998, Bender et al [15] reported ITO/Ag/ITO (IMI) structure with higher conductivity.…”
Section: Introductionmentioning
confidence: 98%
“…45 Durability is known to be a problem. 10 However, the high R NIR of the Au-pigment could not be achieved in the resulting paint.…”
Section: One-dimensional Structuresmentioning
confidence: 99%